Analysis of the Implementation of Accrual-Based Government Accounting and its Implications for the Quality of Financial Reports in the Public Sector - Eka Amelia; Haliah Haliah; Andi Kusumawati (International Journal of Management Research and Economics, 2024)
The aim of this study is to analyze the implementation of accrual-based government accounting and its implications for the quality of financial reports in the public sector. This research uses a qualitative descriptive method, particularly through a literature review using secondary data from previous research journals accessed via Google Scholar. The application of accrual-based accounting in the public sector in Indonesia is a significant step toward improving the quality of financial reports. The analysis shows that the implementation of this system can enhance the transparency, accountability, and accuracy of financial reports. However, challenges in implementation, such as a lack of employee understanding and inadequate information technology infrastructure, need to be addressed. The application of accrual-based accounting in the public sector is a positive and strategic step. By overcoming these challenges, the quality of financial reports can be improved, which will ultimately contribute to better financial management in the public sector.